1948
DOI: 10.6028/jres.041.001
|View full text |Cite
|
Sign up to set email alerts
|

Dipole moments and molecular association of some picrates of primary, secondary, and tertiary amines in benzene and dioxane

Abstract: The dielectric constants of dilute benzene and dioxane solutions of primary, secondar y, and tertiary amine salts of picric acid were measured . Dipole moments are reported fo r the picrates of t h e followingamines ; in benzene: tri-iso-a m yl-(11.9), tTi-n-b uty l-(11.9) , t ri ethyl· (11.7) , di ethylben zyl-(11 .8) , di-n-butyl-(11.5) , di-n-p ropyl-(11. 5) ; in d ioxanc : tr·i-n-butyl-(12.2) , di-n-butyl-(12.1) , n-ocLy l-(12.1), and n-octadecyl-(12.3). The picrates of primary and secondary amincs show a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

1948
1948
1976
1976

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 4 publications
3
10
0
Order By: Relevance
“…The extent ofion-pair association of solutes with identical chain length and anion in o-dichlorobenzene decreases with tncs-eaatng substitution on the nitrogen atom. A similar trend has been observed earlier [3,4] for the butylammonium picrate series in nitrobenzene and probably also in benzene [15]. However, the difference of more than three orders of magnitude in K between didodecyl-and tridodecylammonium chloride found in this work, as compared to only a slight difference in K between Bu~H2 Pic and BuaNH Pic, K = 6.5 X lOs and 5.4 X lOS respectively [3,4], suggest that o-dichlorobenzene is a more "differentiating solvent", while nitrobenzene, due to its higher dielectric constant, is more a "leveling-off" solvent.…”
Section: Methodssupporting
confidence: 59%
“…The extent ofion-pair association of solutes with identical chain length and anion in o-dichlorobenzene decreases with tncs-eaatng substitution on the nitrogen atom. A similar trend has been observed earlier [3,4] for the butylammonium picrate series in nitrobenzene and probably also in benzene [15]. However, the difference of more than three orders of magnitude in K between didodecyl-and tridodecylammonium chloride found in this work, as compared to only a slight difference in K between Bu~H2 Pic and BuaNH Pic, K = 6.5 X lOs and 5.4 X lOS respectively [3,4], suggest that o-dichlorobenzene is a more "differentiating solvent", while nitrobenzene, due to its higher dielectric constant, is more a "leveling-off" solvent.…”
Section: Methodssupporting
confidence: 59%
“…Kraus and co-workers [342] demonstrated that quaternary and tertiary ammonium picrates and halides have large polar (dipole) moments in benzene solution. Subsequently, Maryott [23,343] confirmed this finding and determined the dipole moments of additional salts, including some primary and secondary ammonium picrates. Results of both authors are shown in table 36. It is clear that the dipole moments of the salts are far larger than the moments of the component bases and acids, which are in the range 0-2 D (Debye unit).…”
Section: Dielectric Constantsmentioning
confidence: 92%
“…e/N2, with incr easing dilution indicates tha t the salt is partly dissociated into picric acid and tribenzy1a-mine. The equilibrium constan t for this r eaction , + B Z3NH ... Pi = B z3N + HPi, can be determin ed by a procedure similar to th at describ ed previously [2] . R egarding the change in dielectric constan t as th e sum of three independent contributions that are lin ear functions of the concentrations of the acid, base, and salt, r espectively, • Obtained from least squares solution of eq 3, as shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…S uch acid-base equilibria are well suited for study because of the r elatively large dipole moment of the sal t compared to that of the component acid and base. In a previous investigation of the picrates of various alkylamines of sufficient basic strength to prevent · measurable dissocia tion into fr ee acid and base [2] , it was found that t he picrates of t ertiary amines, but no t those of primary and secondary amines, showed no significant association in benzene. Consequ en tly, association of th e salt should not be a complicating factor in the reaction with tribcnzylamin e. …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation